Digital technologies for open and collaborative teaching. A brief framework - Irina POP-PĂCURAR; Daniela DUMULESCU; Miriam KENYERES (Studia Universitatis Babes-Bolyai, 2023)
The present paper aimed to open a debate about the increasing needs of collaborative learning in digital learning contexts. Collaborative teaching and learning are effective approaches to enhance learning and facilitate students' satisfaction. Digital platforms may help teachers develop collaborative learning environments and provide ways of building various teaching scenarios, promoting autonomous and structured learning contexts. ZUSAMMENNFASSUNG. Dieser Beitrag soll eine Debatte über den wachsenden Bedarf an kollaborativem Lernen in digitalen Lernkontexten eröffnen. Kollaboratives Lehren und Lernen ist ein effektiver Ansatz, um das Lernen zu verbessern und die Zufriedenheit der Studierenden zu fördern. Digitale Plattformen können Lehrkräften dabei helfen, kollaborative Lernumgebungen zu entwickeln und bieten Möglichkeiten, verschiedene Unterrichtsszenarien aufzubauen, die autonome und strukturierte Lernkontexte fördern. Schlüsselwörter: kollaboratives Lehren und Lernen, digitales Lernen, digitale Plattformen, Unterrichtsgestaltung